The long trace of inequality: evidence from Cundinamarca, Colombia (2010)
This paper uses historic data from Cundinamarca, Colombia to empirically assess the impact of land inequality persistence, inherited from the colonial rule, on economic development in the long run. Based on the Engerman & Sokoloff hypothesis and the use of GIS, I use plausible exogenous variation in land endowments to design an instrumental variable strategy. In contrast to recent studies in the literature, I find that more unequal municipalities in the XIX and XX century are associated with better growth and public goods provision measures today. The evidence suggests these results can be explained by political economy channels instead of agricultural productivity gains.